Sustainable Palm Oil Production: A Bibliometric Analysis of Environmental and Economic Perspectives - Hutajulu, Halomoan (Westscience Press, 2025)
Sustainable palm oil production has emerged as a critical global issue due to its significant environmental and economic implications. This study employs a bibliometric analysis using data from Scopus and VOSviewer to examine research trends in sustainable palm oil production, focusing on environmental and economic perspectives. The findings reveal key research themes, including sustainability, biodiversity, oil production, certification, and smallholder participation. The analysis also highlights the dichotomy between economic development and environmental conservation, with strong research clusters examining both ecological impacts and governance mechanisms. Certification programs such as RSPO, ISPO, and MSPO play a crucial role in sustainability efforts, though challenges remain in ensuring equitable access for smallholders. The international co-authorship network suggests limited collaboration between palm oil-producing and consumer nations, underscoring the need for interdisciplinary and cross-national research. The study underscores emerging trends in supply chain transparency and policy interventions as crucial aspects of future sustainable palm oil research. The insights gained from this bibliometric analysis can aid policymakers, researchers, and industry stakeholders in shaping more effective and inclusive sustainability strategies.